Scoping review of the World Health Organization's underlying equity discourses: apparent ambiguities, inadequacy, and contradictions - Michelle M. Amri; Geneviève Jessiman-Perreault; Arjumand Siddiqi; Patricia O'Campo; Theresa Enright; Erica Di Ruggiero (BMC, 2021)
Abstract Background and objective Given the heightened rhetorical prominence the World Health Organization has afforded to equity in the past half-century, it is important to better understand how equity has been referred to and its conceptual underpinning, which may have broader global implications. Eligibility criteria Articles were included if they met inclusion criteria - chiefly the explicit discussion of the WHO's concept of health equity, for example in terms of conceptualization and/or definitions. Articles which mentioned health equity in the context of WHO's programs, policies, and so on, but did not discuss its conceptualization or definition were excluded. Sources of evidence We focused on peer-reviewed literature by scanning Ovid MEDLINE and SCOPUS databases, and supplementing by hand-search. Results Results demonstrate the WHO has held - and continues to hold - ambiguous, inadequate, and contradictory views of equity that are rooted in different theories of social justice. Conclusions Moving forward, the WHO should revaluate its conceptualization of equity and normative position, and align its work with Amartya Sen's Capabilities Approach, as it best encapsulates the broader views of the organization. Further empirical research is needed to assess the WHO interpretations and approaches to equity.